PENGARUH VARIABEL MONETER DALAM NEGERI DAN LUAR NEGERI TERHADAP NILAI TUKAR RUPIAH - M. Fadjri Yansyah; Raja Masbar (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2019)
Abstract The purpose of this study is to see the influence of Indonesian interest rates, American interest rates, Indonesian inflation, American inflation, and BOP position towards rupiah exchange rate. The data used in this study are secondary data such as rupiah exchange rate data, Indonesian and American interest rates, Indonesian and American inflation, and Indonesian BOP during 2003-2017. This study uses the Ordinary Least Square (OLS) model or multiple linear regression to see the effects of Indonesian interest rates, American interest rates, Indonesian inflation, American inflation, and BOP. The results of this research concluded that Indonesian interest rates, American inflation rates, and Indonesian BOP have a negative and significant effect on the exchange rate, where the increases of Indonesian interest rates, American inflation rates, and Indonesian BOP will decrease the nominal of rupiah or appreciation of rupiah towards US dollar. But in this study, Indonesian inflation rates and American interest rates have a positive but unsignificant effect.Keywords: Exchange Rate, Inflation rate, Interest rate, BOP, Monetary Concentration